Pelatihan Bingo Review untuk Joyful English Di Fajar English Course Pare, Kediri - Zuhriyah, Mukimantus; Fajarina, Maskhurin (Fakultas Tarbiyah IAIN Kediri, 2023)
Fajar English Course as one of the course institutions in the English village of Pare has had difficulties in improving the teaching abilities of its tutors. This is because the tutor recruitment system focuses more on alumni of the course institution and those who will still be living in Pare for a long time. So Fajar English Course collaborates with the Community Service team from the English Education Department at Hasyim Asy'ari University to conduct training on teaching strategies using Bingo Review and making teaching materials using the Bingo Review method. After two days of training, the Fajar English Course tutors were able to practice teaching with Bingo Review in speaking, grammar and vocabulary well in microteaching. Apart from that, they are also able to make good teaching materials for speaking, grammar and vocabulary using the Bingo review method. Teaching method training is really needed by Fajar English Course tutors to improve the quality of their teaching. To create a pleasant learning atmosphere, it is highly recommended that English teachers or tutors implement Bingo Review in their respective classes